Faculty's barriers to mentoring freshmen within an interinstitutional context: applying the theory of planned behavior. Issue 5 (20th October 2022) - Huart, Johanne; Leduc, Laurent; Laurent, Nathanaël; Detroz, Pascal; Martynow, Natacha; Charbaut, Célia; Malengrez, Déborah; Vierset, Viviane; Lambert, Isabelle; Gabriel, Laura; Vieujean, Anne-Catherine; Compère, Fabienne; et al.
ABSTRACT: In order to investigate faculties' barriers to mentoring freshmen within an interinstitutional (and possibly reluctant) context, a questionnaire survey (N = 390), based on the Theory of Planned Behavior, was conducted prior to the inception of a wide mentoring program involving nine Belgian higher education institutions. Stepwise multiple regressions pinpointed the predictors of faculty's intention to participate in the program and their underlying beliefs. Results reveal that the obstacles commonly attributed to mentoring in the literature do not necessarily come out of this empirical approach and, conversely, that normative factors, underrepresented in research, can play an important role in resistance to or acceptance of mentoring. These findings contribute to a better knowledge of how likely freshmen instructors are to become involved in a mentoring program. It also has practical applications in helping to anticipate possible difficulties in implementing such a program. Lastly, the paper highlights practical implications for the Belgian consortium.